2017
DOI: 10.1038/s41598-017-08239-9
|View full text |Cite
|
Sign up to set email alerts
|

The Candida albicans HIR histone chaperone regulates the yeast-to-hyphae transition by controlling the sensitivity to morphogenesis signals

Abstract: Morphological plasticity such as the yeast-to-hyphae transition is a key virulence factor of the human fungal pathogen Candida albicans. Hyphal formation is controlled by a multilayer regulatory network composed of environmental sensing, signaling, transcriptional modulators as well as chromatin modifications. Here, we demonstrate a novel role for the replication-independent HIR histone chaperone complex in fungal morphogenesis. HIR operates as a crucial modulator of hyphal development, since genetic ablation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 102 publications
2
22
1
Order By: Relevance
“…The TRNs regulating cell identity also involve unusually large regulatory regions in both fungi and mammals. The median size of mammalian ‘super-enhancers’ is >8 kb versus ~700 bp for typical enhancers 11 , and the regulatory regions of master white-opaque TFs are similarly expanded; the upstream intergenic regions of 6 of the 8 TFs are >7 kb, considerably larger than the average intergenic length of 557 bp in C. albicans 40 . White-opaque TFs bind overlapping regions upstream of the genes encoding the master TFs.…”
Section: Resultsmentioning
confidence: 98%
“…The TRNs regulating cell identity also involve unusually large regulatory regions in both fungi and mammals. The median size of mammalian ‘super-enhancers’ is >8 kb versus ~700 bp for typical enhancers 11 , and the regulatory regions of master white-opaque TFs are similarly expanded; the upstream intergenic regions of 6 of the 8 TFs are >7 kb, considerably larger than the average intergenic length of 557 bp in C. albicans 40 . White-opaque TFs bind overlapping regions upstream of the genes encoding the master TFs.…”
Section: Resultsmentioning
confidence: 98%
“…SOD5 has previously been shown to fall under control of Efg1 [ 13 ]. SOD5 and FRE8 were not identified by ChIP as direct targets of Efg1 or Cph1 [ 43 ] [ 44 ]; both are subject to chromatin remodeling control by Hir1 that works in concert with Efg1 to control genes for morphogenesis [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…We recently demonstrated that hir1 Δ/Δ C. albicans cells have impaired hyphal formation ( Jenull et al, 2017 ). In follow-up experiments, we also analyzed colony morphology in response to fetal calf serum (FCS) on synthetic complete (SC) medium.…”
Section: Resultsmentioning
confidence: 99%
“…HIR acts as transcriptional co-regulator affecting developmental processes in human, animal, or plant cells ( Amin et al, 2013 ; Banaszynski et al, 2013 ; Duc et al, 2015 ; Sadasivam and Huang, 2016 ; Tagami et al, 2004 ) but also regulates gene expression in unicellular yeasts, including S. cerevisiae ( Fillingham et al, 2009 ; Spector et al, 1997 ). As in S. cerevisiae ( Prochasson et al, 2005 ), the C. albicans HIR complex consists of the Hir1, Hir2, Hir3, and Hpc2 subunits ( Jenull et al, 2017 ; Stevenson and Liu, 2013 ). Besides transcriptional repression of histone genes ( Stevenson and Liu, 2013 ), HIR affects sensitivity to antifungal azoles ( Tscherner et al, 2015 ) and hyphal initiation in C. albicans ( Jenull et al, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation